Pembuatan Alat Monitoring Infus Berbasis NodeMCU ESP8266 - Siti Nur Khasanah; Maisyaroh Maisyaroh; Ade Nugraha; Mohamad Ulinnuha (Department of Science and Technology Ibrahimy University, 2021)
The problem of late replacement of infusion mattresses for patients in a medical institution is still common today. It still helps him closely with the nurses' negligence in monitoring the patient's infusion condition. This condition is very dangerous for the patient's health. Therefore the making of infusion monitoring equipment based on NodeMCU esp8266. This tool works by relying on the results of sensor readings that are inserted into the microcontroller which will be processed by NodeMCU. The sensor used in making this system is the sensor module, the sensor reading sensor is the intended emission sensor - in this case, means the drip drops, the sensor will count the number of drops. From the number of drops, it can be used to count the drip infusion. In this study, it can be concluded that the NodeMCU ESP 8266-based infusion monitoring tool using the IR Obstacle sensor component has been successfully made through the functionality test process.